Information Technology: New Generations 13th International Conference on Information Technology - Latifi, Shahram (Advances in Intelligent Systems and Computing, 2016)
This book collects articles presented at the 13th International Conference on Information Technology- New Generations, April, 2016, in Las Vegas, NV USA. It includes over 100 chapters on critical areas of IT including Web Technology, Communications, Security, and Data Mining.